(untitled) (Mūzikas akadēmijas raksti, 2024)
Max Klinger’s Brahms-Phantasie (1894), a volume consisting of fortyone drawings and etchings interspersed with the complete scores of six of Brahms’s vocal works, cemented Klinger’s reputation as the most original artist that Germany has the honor of calling her own (Boetzkes, 1984 : 96), as Hugo von Hofmannstahl declared. In producing the volume, Klinger sought to cast a glance across the range of feeling that he encountered in Brahms’s music, and from there, to sympathize and to go further, to connect and to expand (Kersten, 1993 : 166). By 1894, Klinger had achieved considerable renown as a visual artist. But the Brahms-Phantasie was something more than just another volume of the artist’s famous prints. It was a work to be seen and heard, either literally (when Brahms’s scores are performed) or in the mind of the observer. As such, it exemplified the new, composite art form that Klinger described as Raumkunst or Spatial Art (Klinger, 1987 : 30). Inspired by Richard Wagner’s theory of the Gesamtkunstwerk, Klinger envisioned the Raumkunstwerk as an integral union of artistic media, literally filling the Raum or space inhabited by the observer.